Transformasi Limbah Minyak Jelantah Dalam Pembuatan Sabun Ramah Lingkungan: Program Pengabdian Masyarakat di Desa Wonotenggang - Naili Saadah; Isna Putri Rochmatus Salsabila; Malikah Kautshar Ilmi; Nur Hafidhoh; Siti Halimatus Safitri; Thoyyibatus Sariroh (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Training on making soap from used cooking oil in Wonotenggang Village is an initiative to reduce household waste. The village community showed high enthusiasm in participating in this training. In addition to aiming to reduce waste, this training also provides an opportunity for participants to gain new experiences in managing used cooking oil effectively. Through this activity, the community can utilize the information they have obtained and be able to innovate in making soap from used cooking oil.